Development of a housing for wearable goat peak estrus sensor using finite element analysis - Olegario, Tanya V. (Animo Repository, 2021)
Goat breeding is an increasingly popular source of livelihood in the Philippines. To increase production, goat breeders may practice artificial insemination (AI) which is a breeding technique that allows the rapid spread of genetically superior animals. To fully reap the benefits of AI, it has to be conducted during estrus and more ideally, during the peak estrus which occurs approximately six hours before ovulation. This study aims to design a housing for an intravaginal wearable that can detect this period. A visit to a breeding facility in Isabela State University and various consultations were conducted as part of the data-gathering phase. The rest of the study employed 3D modeling and rapid prototyping techniques. Prototyping for visualization purposes was conducted using fused deposition modeling (FDM) 3D printing but prototypes used on actual goats had to be fabricated differently, using stereolithography (SLA), to ensure the biocompatibility of the material used. A field test was conducted once, in the middle of the study, to test the design on actual goats, and the results from this were used to make improvements for the next iteration. The final design was subjected to finite element analysis (FEA) later in the study.